Unreported truths about COVID-19 and lockdowns Part 1 introduction and death counts and estimates - Berenson, Alex (Coppell, TX: [publisher not identified], 2020)
The author provides a counterweight to media hysteria about coronavirus in this series of short booklets answering crucial questions about COVID. Drawing on primary sources from all over the world, Unreported truths about COVID-19 and lockdowns offers clear, concise and measured answers to some of the most important questions about the coronavirus. -- Adapted from page [4] cover.
Cover title of booklet.
108576
Keywords: 2000-2099; COVID-19 (Disease); COVID-19 (Disease) -- Social aspects; Epidemics -- 21st century; Viruses -- 21st century; Public health -- 21st century